Product Networks, Component Modularity and Sourcing - Anupam Agrawal (Journal of Technology Management & Innovation, 2009)
This paper develops product representations as component networks that evolve from sharing of interfaces with other components in a product and links them to the external world of sourcing. The paper formally defines and develops two measures of component modularity by linking Graph Theory and Product Architecture principles. The first measure, degree modularity, is related to the strength of design dependencies with adjacent components. The second measure, bridge modularity, is related to the criticality of components. These two component modularity measures are calculated and interpreted by studying the actual product architecture of two products - a small machinery product and an automobile subsystem. A sourcing framework is suggested, treating product obsolescence as a moderating variable in the effect of modularity on sourcing. The paper concludes with a discussion of how component modularity measures can help managers to take better decisions in the arena of sourcing – both at an operational level and at the strategic level. Directions for future work are discussed.